Surface and defect structure of oxide nanowires on SrTiO3. - Marshall, MS; Becerra-Toledo, A; Marks, L; Castell, M (2011)
Processing the SrTiO(3)(001) surface results in the self-assembly of reduced titanate nanowires whose widths are approximately 1 nm. We have imaged these nanowires and their defects at elevated temperatures by atomic resolution scanning tunneling microscopy. The nanowire structure is modeled with density functional theory, and defects observed in the center of the nanowire are determined to be Ti(4)O(3) vacancy clusters. The activation energy for Ti(4)O(3) vacancy cluster diffusion is explicitly measured as 4.98±0.17 eV with an exponential prefactor of μ=6.57×10(29) (s(-1).